Pengaruh Citra Merek, Promosi dan Persepsi harga Terhadap Keputusan Pembelian di MCDonald’s Grand Wisata Tambun - Sudarman Sudarman; Heidi Reza Ruliarto (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
In the restaurant sector, the consumer's decision to purchase plays a crucial role in a company's existence, particularly for Mcdonald’s, as it directly affects profitability. The objective of this study is to examine the effects of brand image (X1), promotion (X2), and price perception (X3) as predictor variables on the purchase decisions (Y) made at Mcdonald’s Grand Wisata Tambun. This research adopts a quantitative research design based on surveys and employs an accidental sampling method, with a sample size of 100 individuals who have previously made purchases at Mcdonald’s Grand Wisata Tambun. Multiple regression analysis is employed to analyze the data acquired from the participants, and the primary data is directly gathered from the respondents. Research findings show that, independent variables affect purchase decision simultaneously at Grand Wisata Tambun. However, partially brand image, promotion, and price perception affect significantly purchase decision at Mcdonald’s Grand Wisata Tambun.